LncRNA TUG1 promotes hypertrophic scar formation via the miR-627/IGF1R axis - Zeming Bai; Ziyang Han; Xiangzi Kong; Rirui Zhao; Haiwei Sun; Hai Huang; GuYue Wang; Zhe Li; Kai Tao; Jiulong Liang (Journal of Molecular Histology, 2026)
Hypertrophic scars (HS) are fibrotic skin disorders driven by abnormal fibroblast activity. The molecular mechanisms underlying HS remain incompletely understood, particularly the role of non-coding RNAs. Expression levels of lncRNA TUG1, miR-627, and IGF1R were measured in HS tissues and fibroblasts using qRT-PCR and Western blotting. Dual-luciferase assays validated direct interactions. Functional effects of TUG1 and miR-627 on fibroblast proliferation and migration were assessed using MTT and Transwell assays. A rabbit ear model of HS was used to examine in vivo effects of TUG1 and miR-627 modulation on scar formation and molecular expression. TUG1 was significantly upregulated in HS tissues and inversely correlated with miR-627, which was downregulated. TUG1 promoted fibroblast proliferation and migration by directly sponging miR-627, thereby lifting repression on IGF1R, a known pro-fibrotic effector. Luciferase assays confirmed direct binding of miR-627 to both TUG1 and IGF1R. Co-transfection of miR-627 attenuated TUG1-induced IGF1R upregulation and reversed its pro-fibrotic cellular effects. In vivo, TUG1 overexpression led to increased scar thickness, collagen deposition, and IGF1R expression, while miR-627 overexpression mitigated these effects. Co-administration of both restored scar morphology and molecular markers to near-control levels. TUG1 promotes hypertrophic scar formation by sponging miR-627 and derepressing IGF1R. This newly identified TUG1–miR-627–IGF1R axis plays a central role in HS pathogenesis and may serve as a promising therapeutic target for fibrotic skin disease.

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)